REGULASI DIRI DALAM BELAJAR DAN ACADEMIC BURNOUT PADA SISWA SMA GLOBAL ISLAMIC BOARDING SCHOOL - Andi Zainuddin Japeri; Udi Rosida Hijrianti (Universitas Muhammadiyah Lampung, 2022)
Boarding school students, are prone to experiencing academic burnout, a psychological condition where individuals feel tired, apathetic, and cynical about their academic activities. Boarding school students need self-regulation in learning, individual efforts to manage thoughts, feelings, and actions to achieve learning goals. This study aims to determine the relationship of self-regulation in learning with academic burnout in GIBS high school students. The research subjects were GIBS High School students totaling 160 students. The sampling technique used was Stratified Proporsional Random Sampling. The data collection method used the self-regulation scale in learning and the academic burnout scale. The analysis test uses pearson's product moment correlation. The results showed the correlation value (r= -0.370; sig= .000 (p<0.05)) thus the hypothesis was accepted. This means that the higher self-regulation in student learning, the lower the academic burnout experienced by students